NORDEK : plán severské hospodářské spolupráce v letech 1968–1970 - Jiří Pokorný (Studia Historica Brunensia, 2013)
The study "NORDEK: Plan of Nordic Economic Cooperation in 1968–1970" is focused on development of Nordic cooperation at the end of 60's and its consequences in European integration of Nordic states at the beginning of 70's.